THE SECOND HALF OF THE XVIII CENTURY AND IN THE MIDDLE OF THE XIX CENTURY IN THE BUKHARA EMIRATE COINAGE AND ITS SOCIO-ECONOMIC SIGNIFICANCE - Khasanov Murod Gaybullayevich (PalArch's Journal of Archaeology of Egypt / Egyptology, 2020)
This article is about the socio-economic situation of the Bukhara state in the second half of the XVIII century, the monetary reform carried out by Emir Shahmurad, the minting of coins by the Bukhara emirs from the 80s to the middle of the XIX century and the role of monetary policy in the country's socio-economic life.